2022
DOI: 10.3390/app12146876
|View full text |Cite
|
Sign up to set email alerts
|

Computational Methods for Neuron Segmentation in Two-Photon Calcium Imaging Data: A Survey

Abstract: Calcium imaging has rapidly become a methodology of choice for real-time in vivo neuron analysis. Its application to large sets of data requires automated tools to annotate and segment cells, allowing scalable image segmentation under reproducible criteria. In this paper, we review and summarize the most recent methods for computational segmentation of calcium imaging. The contributions of the paper are three-fold: we provide an overview of the main algorithms taxonomized in three categories (signal processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Current methods of neuron segmentation have a trade-off between accuracy and manual effort: supervised methods have superior accuracy but require substantial manual effort to generate ground truth labels for each imaging condition ( Abbas and Masip, 2022 ). This work developed SAND, the first semi-supervised pipeline to segment active neurons from two-photon calcium recordings with limited ground truth labels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current methods of neuron segmentation have a trade-off between accuracy and manual effort: supervised methods have superior accuracy but require substantial manual effort to generate ground truth labels for each imaging condition ( Abbas and Masip, 2022 ). This work developed SAND, the first semi-supervised pipeline to segment active neurons from two-photon calcium recordings with limited ground truth labels.…”
Section: Discussionmentioning
confidence: 99%
“…Both supervised and unsupervised machine learning methods exist for neuron segmentation ( Abbas and Masip, 2022 ; Bao and Gong, 2023 ). Supervised methods consist of convolutional neural networks (CNNs), while unsupervised methods include dictionary learning, PCA/ICA, and matrix factorization [e.g., CaImAn ( Giovannucci et al, 2019 ) and Suite2p ( Pachitariu et al, 2017 )].…”
Section: Introductionmentioning
confidence: 99%
“…There are already several algorithms for registration and ROI segmentation of neural cell bodies in two-photon calcium imaging data. 71 Here we summarize particularly important papers on real-time use. Mitani and Komiyama 48 completed motion correction of 1000 video frames in and showed that such processing can be applied to BMIs.…”
Section: Brain Machine Interfaces Using In Vivo Mu...mentioning
confidence: 99%